Cardiac Adaptation to Prolonged High Altitude Migration Assessed by Speckle Tracking Echocardiography - Chen, Xu; Liu, Bohan; Deng, Yujiao; Yang, Feifei; Wang, Wenjun; Lin, Xixiang; Yu, Liheng; Pu, Haitao; Zhang, Peifang; Li, Zongren; Zhong, Qin; Jia, Qian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Exposure to high altitudes represents a physiological stress that leads to significant changes of cardiovascular properties. However, long-term cardiovascular adaptions to high altitude migration of lowlanders have not been described. Accordingly, we measured changes of cardiovascular properties following prolonged hypoxic exposure in acclimatized Han migrants and Tibetans. Methods: Echocardiographic features of recently adapted Han migrants (3-to-12 months, n=64) and highly adapted Han migrants (5-to-10 years, n=71) residence in Tibet (4300 meters) using speckle tracking echocardiography were compared to those of age-matched native Tibetans (n=75) and Han lowlanders living at 1400 meters (n=60). Results: Short-term acclimatized migrants showed increased estimated pulmonary artery systolic pressure (PASP) (32.6±5.1mmHg vs. 21.1±4.2mmHg, p<0.05), enlarged right ventricles (RVs), decreased fractional area change (FAC) with decreased RV longitudinal strain (-20±2.8% vs -25.5±3.9%, p<0.05). While left ventricular ejection fraction (LVEF) was preserved, LV diameter (41.7±3.1mm vs. 49.7±4.8mm, p<0.05) and LV longitudinal strain (-18.8±3.2% vs. -22.9±3.3%, p<0.05) decreased. Compared with recent migrants, longer-term migrants had recovered RV structure and functions with slightly improved RV and LV longitudinal strain, though still lower than lowlander controls; LV size remained small with increased mass index (68.3±12.7 vs. 59.3±9.6, p<0.05). In contrast, native Tibetans had slightly increased PASP (26.1±3.4mmHg vs. 21.1±4.2mmHg, p<0.05) with minimally altered cardiac deformation compered to lowlanders. Conclusions: RV systolic function is impaired in recent (<1 year) migrants to high altitudes but improves during long-term dwelling. LV remodeling persists in long-term migrants (>5 years) but without impairment of LV systolic or diastolic function. In contrast, cardiac size, structure and function of native Tibetans are more similar to those of lowland dwelling Hans.